Small mammal owners’ experiences of housing challenges and animal welfare: A COM-B and word frequency analysis - Grace Carroll; Kerry Taylor; Claire Stallard; Alison Wills (Animal Welfare)
Small mammals are particularly dependent on owner-provided housing and husbandry yet are frequently kept in conditions that do not meet their welfare needs. This study used the COM-B model (Capability, Opportunity, Motivation = Behaviour) to identify behavioural drivers influencing housing provision among 723 UK small mammal pet owners. This model of human behaviour proposes that behaviour occurs when individuals have the capability, opportunity, and motivation to act. Owners of the eight most commonly kept small mammal species were surveyed: rabbits (Oryctolagus cuniculus), guinea pigs (Cavia porcellus), hamsters (Cricetinae), gerbils (Gerbillinae), rats (Rattus norvegicus), mice (Mus musculus), chinchillas (Chinchilla lanigera), and degus (Octodon degus). Opportunity, particularly the availability of suitable enclosures, emerged as the primary barrier, while Capability and Motivation were identified as facilitators, with most pet owners willing and able to provide good levels of welfare. Owner approaches to assessing health and welfare at home were examined through qualitative word frequency analysis, with responses mapped to the Five Domains model. This analysis focused on rabbits, guinea pigs, rats, and hamsters due to limited data availability for other species. Overall, behavioural indicators were most commonly used to identify positive health and welfare, while nutritional and physical signs were cited most frequently for negative states. Changes in eating behaviour were the most frequently cited indicators of ill health or poor welfare across all four species, suggesting this may serve as a practical health and welfare indicator for owners. Improving access to suitable housing and further exploring eating behaviour as an early health and welfare indicator may together support better husbandry for small mammal pets.